A single early-life seizure results in long-term behavioral changes in the adult Fmr1 knockout mouse - Hodges, Samantha L.; Reynolds, Conner D.; Nolan, Suzanne O.; Huebschman, Jessica L.; Okoh, James T.; Binder, Matthew S.; Lugo, Joaquin N. (Epilepsy research, 2019)
•Early-life seizures increased repetitive behavior in adult wild type (WT) mice.•Repetitive behavior in Fmr1 knockout mice was not exacerbated following seizures.•Deletion of Fmr1 and seizures had opposite effects on prepulse inhibition.•Early-life seizures resulted in reduced sociability in adult WT mice.•An early-life seizure enhanced hippocampal-dependent learning in adult WT mice. Fragile X syndrome (FXS) is the leading cause of inherited intellectual disability and a significant genetic contributor to Autism spectrum disorder. In addition to autistic-like phenotypes, individuals with FXS are subject to developing numerous comorbidities, one of the most prevalent being seizures. In the present study, we investigated how a single early-life seizure superimposed on a genetic condition impacts the autistic-like behavioral phenotype of the mouse. We induced status epilepticus (SE) on postnatal day (PD) 10 in Fmr1 wild type (WT) and knockout (KO) mice. We then tested the mice in a battery of behavioral tests during adulthood (PD90) to examine the long-term impact of an early-life seizure. Our findings replicated prior work that reported a single instance of SE results in behavioral deficits, including increases in repetitive behavior, enhanced hippocampal-dependent learning, and reduced sociability and prepulse inhibition (p <  0.05). We also observed genotypic differences characteristic of the FXS phenotype in Fmr1 KO mice, such as enhanced prepulse inhibition and repetitive behavior, hyperactivity, and reduced startle responses (p <  0.05). Superimposing a seizure on deletion of Fmr1 significantly impacted repetitive behavior in a nosepoke task. Specifically, a single early-life seizure increased consecutive nose poking behavior in the task in WT mice (p <  0.05), yet seizures did not exacerbate the elevated stereotypy observed in Fmr1 KO mice (p >  0.05). Overall, these findings help to elucidate how seizures in a critical period of development can impact long-term behavioral manifestations caused by underlying gene mutations in Fmr1. Utilizing double-hit models, such as superimposing seizures on the Fmr1 mutation, can help to enhance our understanding of comorbidities in disease models.